Context and wine quality effects on consumers' mood, emotions, liking and willingness to pay for Australian Shiraz wines. (November 2016) - Danner, Lukas; Ristic, Renata; Johnson, Trent E.; Meiselman, Herbert L.; Hoek, Annet C.; Jeffery, David W.; Bastian, Susan E.P.
Abstract: This study investigated the effect of different contexts on consumers' mood, product-evoked emotions, liking and willingness to pay for wine. Three consumer trials (n = 114, 115, and 120) examined 3 different sample sets of 4 Australian commercial Shiraz wines. Each sample set was comprised of a high, medium-high, medium-low and low quality wine as designated by an expert panel. Wine consumers evaluated the same set of wines in the three different contexts, ranging from a highly-controlled laboratory setting to more realistic restaurant and at-home settings. Results showed that high quality wines were liked more and elicited more intense emotions of positive valence compared to wines of lower quality. Context effects were observed on emotions, but not on liking, indicating that although emotions and liking are correlated, the measurement of emotions can deliver additional information over liking. Tasting wine in the restaurant context evoked more intense positive emotions compared to the home and laboratory contexts. Participants' mood before tasting the wines had a strong influence on consecutive product-evoked emotion ratings, but only weak influence on liking ratings. Furthermore, a strong relationship between wine-evoked emotions and willingness to pay was observed, showing that if a wine-evoked more intense emotion of positive valence e.g., contented, enthusiastic, happy, optimistic and passionate participants were willing to pay significantly more for a bottle. Additionally, the absence of negative emotions, even if typically evoked to a very weak extent, is a requirement for an increased willingness to pay. This study indicates it is worthwhile to consider context and emotions in wine testing and marketing. Graphical abstract: Highlights: The Australian Wine Evoked Emotions Lexicon (AWEEL) was developed and applied. Wine of four quality levels were evaluated in three different consumption contexts. Consumption context influenced consumers' emotions but not liking. High quality wine evoked more intense positive emotions compared to lower quality. A strong relationship between evoked emotions and willingness to pay was found.